Penyaluran Zakat Fitrah Masyarakat Desa Banyuwangi Kecamatan Cigudeg Bogor dalam Tinjauan Hukum Islam - Sadiah, Umayah; Irsan, Irsan (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
The purpose of this study was to determine the practice of distributing zakat fitrah in Banyuwangi Village and its review from Islamic law. The approach used is a qualitative approach, primary data was taken through interviews with the Banyuwangi Village community, direct observation and related literature as supporting data. The results of the study indicate that the distribution of zakat fitrah is intended for religious teachers, midwives, and zakat committees; zakat is given in the form of money in the last 10 days; and there is a special wording at the time of zakat handover. The concept of distributing zakat fitrah that occurs in the field is known to not be fully in line with Islamic law, considering several things: 1) not all have been distributed to the mustahiq, 2) the form of zakat issued is not fully appropriate, and 3) there is a special wording in the contract. Some evaluations that must be done are the recipients of zakat fitrah given to the mustahiq: the poor or needy, zakat fitrah given in the form of staple foods, distributed before the 'Eid prayer or one or two days before the Eid, and there is no special wording in the contract. In addition, the zakat committee in Banyuwangi Village cannot be called amil zakat because it is not registered with BAZNAZ, so it cannot take part of the zakat